TOTAL EDENTATION TREATMENT USING MOBILE IMPLANT-SUPPORTED TOTAL DENTURES - Vadim Oineagra; Kamel Earar; Oleg Solomon; Trifăuțanu Petru; Vasile Oineagra; Vasile Rusuv; Andrei Fachira; Galina Pancu (Romanian Society of Oral Rehabilitation, 2022)
12 (8 m., 4 w.) patients, aged between 55 and 75 years, with different forms of total edentia, uni and/or bimaxillary , were selected, complexly examined and treated prosthetically. It was found that, because the clinical picture of total edentulism is determined by a series of involutive processes (atrophy, resorption), its prosthetic treatment requires the consideration of numerous retention factors (physical, mechanical, physiological). The correct evaluation of these factors will ensure the requirements of all the fundamental principles of biomechanics, respectively the integration of the prosthetic part with the elements of the stomatognathic system and of the body in general.